Preparation and Evaluation of Tretinoin Microemulsion Based on Pseudo-Ternary Phase Diagram - Fatemeh Leis; Anayatollah Salimi; Eskandar Moghimipour (Tabriz University of Medical Sciences, 2012)
Purpose: The aim of the present research was to formulate a transparent microemolsion as a topical delivery system for tretinoin for the treatment of acne. Methods: Microemulsion formulations prepared by mixing appropriate amount of surfactant including Tween 80 and Labrasol, co-surfactant such as propylene glycol (PG) and oil phase including isopropyl myristate - transcutol P (10:1 ratio). The prepared microemolsions were evaluated regarding their particle size, zeta potential, conductivity, stability, viscosity, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), refractory index (RI) and pH. Results: The results showed that maximum oil was incorporated in microemolsion system that was contained surfactant to co-surfactant ratio (Km) of 4:1. The mean droplets size range of microemulsion formulation were in the range of 14.1 to 36.5 nm and its refractory index (RI) and pH were 1.46 and 6.1, respectively. Viscosity range was 200-350 cps. Drug release profile showed 49% of the drug released in the first 8 hours of experiment belong to ME-7. Also, Hexagonal and cubic structures were seen in the SEM photograph of the microemulsions. Conclusion: physicochemical properties and in vitro release were dependent upon the contents of S/C, water and, oil percentage in formulations.Also, ME-7 may be preferable for topical tretinoin formulation.